The Role of Class Teachers in Improving Students' Social Intelligence at SDN Kedungsari 1 Kediri - Diaz, Davin Valva; Rapita, Desinta Dwi (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2026)
This study aims to describe the role of classroom teachers in improving the social intelligence of students at SDN Kedungsari 1 Kediri. This study uses a descriptive qualitative method to provide descriptive results on the role of classroom teachers in improving social intelligence in the learning process. The data sources for this descriptive qualitative study were obtained from primary data, namely the results of interviews with classroom teachers. The data analysis techniques used involved collecting data, reducing it, presenting it, and drawing conclusions. The results of the study show that the role of classroom teachers at SDN Kedungsari 1 Kediri is as managers, meaning that classroom teachers act as managers who manage learning in the classroom, create a comfortable learning atmosphere, and organize the classroom according to the needs of students. teachers as mentors, who provide guidance, counseling, and support to students in social and knowledge aspects, and teachers as motivators, who provide encouragement and enthusiasm to students to further enhance their social intelligence in the school environment and classroom environment in particular. Keywords: Role, role of classroom teachers, social intelligence.